2008
DOI: 10.1164/rccm.200708-1291oc
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for Fibronectin Extra Type III Domain A in Pulmonary Fibrosis

Abstract: Rationale: Tissue fibrosis is considered a dysregulated wound-healing response. Fibronectin containing extra type III domain A (EDA) is implicated in the regulation of wound healing. EDA-containing fibronectin is deposited during wound repair, and its presence precedes that of collagen. Objectives: To investigate the role of EDA-containing fibronectin in lung fibrogenesis. Methods: Primary lung fibroblasts from patients with idiopathic pulmonary fibrosis or from patients undergoing resection for lung cancer we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
259
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(265 citation statements)
references
References 37 publications
5
259
1
Order By: Relevance
“…This same mutation has been reported in a 34-year-old man with moderate aplastic anemia that did not respond to immunosuppression and has short telomere lengths as measured by flow-fluorescence in situ hybridization (8). The development of pulmonary fibrosis versus bone marrow dysfunction in telomerase mutation carriers may be related to secondary ''hits,'' such as environmental toxins (cigarette smoking), fibrosis-prone intrinsic host mesenchymal responses to injury (34,35), or other susceptibilities. Understanding the influences on the development of lung disease in telomerase mutation carriers will be important to delineate.…”
Section: Table 3 Distribution Of Case Subects and Control Subjects Ssupporting
confidence: 52%
“…This same mutation has been reported in a 34-year-old man with moderate aplastic anemia that did not respond to immunosuppression and has short telomere lengths as measured by flow-fluorescence in situ hybridization (8). The development of pulmonary fibrosis versus bone marrow dysfunction in telomerase mutation carriers may be related to secondary ''hits,'' such as environmental toxins (cigarette smoking), fibrosis-prone intrinsic host mesenchymal responses to injury (34,35), or other susceptibilities. Understanding the influences on the development of lung disease in telomerase mutation carriers will be important to delineate.…”
Section: Table 3 Distribution Of Case Subects and Control Subjects Ssupporting
confidence: 52%
“…Mechanistically, the authors identified a critical role for matrix-dependent suppression of miR-29 in engaging increased translation of matrix proteins when fibroblasts were seeded on IPF-derived matrices (5), elucidating a mechanism by which fibrotic matrix programs cells to produce greater amounts of matrix (Figure 1). Delineating the profibrotic cues that exist within pathological matrices will require intensive efforts, but several matrix or matrixassociated protein candidates have been identified that confer profibrotic signals and correlate with fibrotic pathologies (2), including fibulin-1 (10), osteopontin (11,12), periostin (13,14), connective tissue growth factor (15), and fibronectin (16,17).…”
Section: Matrix and Mesenchyme In Lung Diseasesmentioning
confidence: 99%
“…The protein fibronectin (FN) is a major component of the ECM, and an excessive and disordered FN matrix is present in fibrotic diseases (15) and hypertrophic scars (16). FN matrix assembly is mediated by integrin receptors and regulated by intracellular signals, cytoskeletal organization, and availability of FN (17).…”
Section: The Extracellular Matrix (Ecm)mentioning
confidence: 99%